Entre El Deber y El Sufrimiento: Sentimientos De Los Profesionales De Enfermería En La Atención De Pacientes Con Sars Cov-2 Hospitalizados En Uci - Romero Mendoza, Julieth Paola; Rubio Rodriguez, Marta Milena (Universidad Antonio Nariño, 2022)
Covid-19 is a viral disease that appeared as cases of severe pneumonia with unknown etiology and that, due to its high transmissibility, generated a pandemic that collapsed hospital services worldwide and generated a greater workload for health and medical personnel. particularly for nursing professionals, who have experienced mental health problems. It is within the framework of this context that an integrative review of the literature is proposed, with the aim of identifying the state of knowledge related to the feelings of nursing professionals in the care of patients with Sars Cov-2, hospitalized in intensive care units. For the integrative review, the most important databases were used and the search equations were constructed that allowed the collection of the most relevant literature related to the subject. For this, three filters were used; the first, contemplated the selection of documents through the search equations generated; the second, was carried out from the critical reading of the abstracts to identify the articles related to the topic and the research question; and the third, applied the CASPe tool (Critical Appraisal Skills Program Spanish) to identify the studies with greater consistency and validity, in this way, finally, updated knowledge regarding the mental health of nursing professionals was recovered